The Effect of Medication Reconciliation Process on Medication Errors at Medical Ward in Sungai Kolok Hospital - Keawmang, Kanchana (Princess of Naradhiwas University Journal, 2025)
The objectives of this retrospective descriptive study were to examine the effect of the medication reconciliation process, the quantity, nature, and degree of severity of medication errors, as well as the correlation between medication reconciliation and the type and magnitude of medication errors that occurred in the medical ward. Patients with past medication histories who were admitted to the medical ward at Sungai Kolok hospital between October 1, 2022, and September 30, 2023, served as samples of this study. Data was gathered from the hospital data-based system and the medication reconciliation form. Based on inclusion and exclusion criteria, the results showed that 1360 samples of 2760 patients had a history of medical usage prior to admission. The majority of 1008 patients had either hypertension alone or hypertension in conjunction with another illness. Pharmacists discovered medication errors in 324 patients throughout the admission period and 134 patients during the hospital discharge procedure. The three highest levels of medication errors were ordering medications that were not on the hospital list, making omission errors, and changing the dosage and mode of medication use. Only medication errors in severity levels B and C were discovered. Analyzing the relationship between medication reconciliation and the type and magnitude of medication errors revealed that there were statistically significant relationships between medication reconciliation and medication errors found in each severity level (p < 0.001) and the medication reconciliation process had statistically significant relationships with the type of medication errors regarding commission errors (P-value = 0.042). However, in this study no statistically significant relationship was found between the medication reconciliation process with other types of medication errors.